Pengaruh Kualitas Layanan, Fasilitas dan Lokasi terhadap Keputusan Menginap Tamu di Pade Hotel Aceh Besar - Mella, Reckyanto; Hulu, Meitolo (CV. Creative Tugu Pena, 2023)
The number of visits is decreasing because in addition to the impact of the pandemic, but visitors' interest in staying at the Pade Hotel Aceh has also decreased. Friendly and responsive service can increase guest satisfaction. Location is a key factor influencing stay decisions, while hotel facilities also play an important role in determining customer comfort and satisfaction. This study aims to identify the effect of service quality, facilities, and location on stay decisions at the Pade Hotel Aceh. There were 100 respondents in this study where participants included all visitors who stayed at Pade Hotel Aceh. The results showed a significant influence of Service Quality and Location on visitors' Staying Decisions. Meanwhile, the Facility factor proved to have no significant effect on the Staying Decision. The measurement of the representation of this research variable is 66.2% so it is necessary to consider other additional factors related that can influence visitors' decisions to stay. Keywords: Service Quality, Stay Decision, Service Quality Facilities